Pilgrimage: An Image of Mediaeval Religion - Sumption, Jonathan (London Faber & Faber, 1975)
In a fascinating work of history, Jonathan Sumption brings alive the traditions of pilgrimage prevalent in Europe from the beginning of Christianity to the end of the fifteenth century. Vividly describing such major destinations as Jerusalem, Rome, Santiago de Compostela and Canterbury, he examines both major figures - popes, kings, queens, scholars, villains - and the common people of their day. With great sympathy he evokes their achievements and failures, and addresses the question of what motivated such extraordinary quests.
Keywords: Middle Ages (500-1400); Cuckoo; Religion